Harmful oral suction habits in children: association with breastfeeding and family social profile - Moimaz, Suzely Adas Saliba [UNESP]; Lolli, Luiz Fernando [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Saliba, Orlando [UNESP]; Saliba, Nemre Adas [UNESP]; Azevedo, Poliane da Silva [UNESP] (FapUNIFESP (SciELO), 2010)
Purpose: To record the prevalence of nonnutritive sucking habits (thumb and pacifier sucking) in children at 6 and 12 months of age and test its association with family social profile and breastfeeding pattern. Method: The sample consisted of 80 pairs of mother-child living in the Northwest region of the state of São Paulo, Brazil. A semi-structured questionnaire was used to collect data on the presence of nonnutritive sucking habits, family social profile and breastfeeding pattern when the children had 6 and 12 months of age. Data were analyzed by using qui-square tests. Results: Pacifier sucking was more frequent than thumb sucking. Exclusive breast feeding was not reported for children either in the 6th or 12th month of age, and approximately 70% were already receiving artificial feeding. There was no association between family social profile and sucking habits, but lower rates of breastfeeding was associated with pacifier sucking in the 12-month old children. Thumb sucking was not associated with breastfeeding. Conclusion: The frequency of breastfeeding was lower than that recommended by WHO for children in the age groups assessed. Pacifier sucking was more prevalent than thumb sucking and was associated with a lower rate of breastfeeding in the 12th-month old children. Family social profile does not seem to be related with nonnutritive sucking habits.

Objetivo: Registrar o padrão de aleitamento materno, o padrão familiar social e os hábitos de sucção deletérios (chupeta e dedo) em crianças com 6 e 12 meses de idade e testar a associação desses fatores. Metodologia: A amostra foi composta por 80 pares de mãe-criança, residentes da região do noroeste do estado de São Paulo, Brasil. Utilizou-se um questionário semi-estruturado para a coleta de dados de presença ou não de hábito de sucção de chupeta e/ou dedo, tipo de aleitamento e padrão familiar social quando as crianças tinham 6 e 12 meses de idade. Os dados foram analisados estatisticamente por testes qui-quadrado. Resultados: Nenhuma criança esteve sob aleitamento materno exclusivo ao 6º e ao 12º mês de idade; 69% já estavam recebendo aleitamento artificial. Mais da metade da amostra (n=52) relatou ao menos um hábito de sucção deletério, sendo que a chupeta foi mais prevalente que a sucção digital. Houve associação entre menor taxa de aleitamento ao 12º mês e sucção de chupeta, mas a sucção digital não interferiu no aleitamento materno. Conclusão: O padrão de aleitamento materno esteve abaixo do recomendado pela OMS para o período correspondente. A sucção de chupeta foi mais prevalente que a digital e ao 12º mês esteve associada à menor taxa de aleitamento materno.
Hábitos bucais de sucção deletérios em crianças: associação com padrão de aleitamento e perfil social familiar
Keywords: Breast feeding; Sucking habits; Aleitamento materno; Hábitos de sucção